Analisis Kesulitan Belajar Siswa Tunanetra Pada Pelajaran Ekonomi Di SMA Kertajaya Surabaya - Sofiyatil Ilmi MB (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to find out the learning difficulties of blind students in Economics lessons. This research method uses a qualitative descriptive type, while data collection uses interviews with four blind students at SMA Kertajaya Surabaya with direct interviews. Data collection techniques using purposive and snowball sampling. The results of the study show that especially for blind students, the Economics Teacher provides additional learning media in the form of files or video links from YouTube which can help them to understand Economics material auditory. Then to work on economics assignments, blind students use cell phone media. The Economics teacher provides media to collect special assignments for blind students via the WhatsApp application. Giving assignments or exam questions will be read out by the teacher then the blind students work on documents (not written on paper).